Assessment of the Status of Local Markets Infrastructure in the Dodoma Central Business District Tanzania - Babune, George Julius (Journal of Advanced Research in Humanities and Social Sciences, 2023)
The study examined the status of local markets infrastructure in Dodoma Central Business District. It is contended that markets are important centres for socio-economic aspects of both the Dodoma City and people’s livelihoods. It intended to find out how the Dodoma City facilitates the operation of markets in terms of markets location, problems inherent and the status of revenue and infrastructure of the market centres. It employed the cross-sectional design whereby a mixed approach was employed in the process. Data were generated using interviews, observation, documentary review, and focus group discussions methods with the former Dodoma Municipal Council (DMC) Officials, Sellers, and buyers of Majengo, Sabasaba, and Bonanza Markets. It was found that in DMC, markets are unevenly distributed from Central Business District. Factors for the location being population growth that had resulted in the current distribution based on centrality and distance from residences and from markets, land use and accessibility to roads. Markets have valuable revenue generation that is not internalized for their development. It concluded that markets have a great contribution to DMC revenue, yet they had received poor infrastructural management and poor participation of sellers. The study recommended the need for DMC to use effectively the Public-Private Partnership in the management of local markets. This will redistribute the population by establishing urban centres that will add on revenue to own source of Dodoma Municipal Council.